Meeting the obligation to communicate clinical trial results to study volunteers. Issue 2 (March 2012) - Getz, Kenneth; Hallinan, Zachary; Simmons, Diane; Jo Brickman, Marla; Jumadilova, Zhanna; Pauer, Lynne; Wilenzick, Marc; Morrison, Briggs
Although the overwhelming majority of study volunteers want to receive information on the results of their participation in clinical trials, research suggests that most study volunteers never do. CISCRP – an independent nonprofit organization – in collaboration with Pfizer, conducted a study evaluating the feasibility and impact of a new process to inform study volunteers of the results of their clinical trials. Two process components were evaluated via surveys, focus groups, and interviews with volunteers and investigative site staff: a series of ongoing post-trial communications to set expectations for when trial results would be received; and routine development and delivery of the lay language trial results summary. The results of this assessment show that study volunteers and investigative site staff are extremely receptive to receiving clinical trial results and that the process of preparing and disseminating clinical trial results is feasible and generally easy to execute. The results also indicate that study volunteer comprehension of basic facts about their clinical trial pre- and post-test increased by as much as 65.6 percentage points, and suggest that this communication initiative may positively impact volunteer recruitment, retention and long-term trust in the clinical research enterprise.